The Teaching of English Conversation at Oxford Public School Morarkhera: A Case Study in India - Muhammad Wahid (Journal of English Language Teaching and Linguistics, 2023)
This study was intended to describe the phenomenon of the implementation of the teaching of English conversation at Oxford Public School Morarkhera in India. Case study qualitative research was implemented in this study.  To gain the data, the subjects of the study were chosen. The subjects in this study were the students of Oxford Public School Morarkhera who took the English Conversation class. They were from first grade to fifth grade. Data collection instruments used are interviews, observation, and documentation. Data analysis was analyzed using the model of Miles et al. consists of four stages, namely the data collection, data condensation, data display, and conclusion drawing. The results show a lower percentage of speaking lessons at the school, which can be attributed to the priority given to reading and writing. In the first year, only 50% of the available teaching material is devoted to speaking, as it is considered the second skill to be mastered by students. Nevertheless, speaking skills must not be neglected in the English curriculum. The portion is sufficient as speaking activities will be integrated with other English skills. The teacher primarily uses English rather than Hindi during the teaching-learning process, which can lead to student stress due to a lack of comprehension. It is important for students to participate actively in speaking class activities, as mastering the English language, particularly speaking skills, is crucial for their success. The finding suggests that the communicative approach may require adaptation, and the schools should create an environment that supports and encourages English-speaking mastery among their students.